Multibeam Mapping of the Reykjanes Ridge: Volcano Tectonic Structures Between 57°5' and 58°5'N - Rocha, Renata, 1991- (2017)
The Reykjanes Ridge, extending from Iceland to approximately 55°N, is the northernmost part of the Mid-Atlantic ridge. This region represents the tectonic boundary between the North American and Eurasian tectonic plates in combination with the Icelandic mantle hotspot, and therefore has very high volcanic activity. It is an anomalous mid-ocean ridge, with an axis-parallel morphology and the lack of transform faults, converging to its axis on approximately 58N. Such places are widely unexplored and might reserve important mineral resources. On this wok, we use new multibeam data to describe and analyze some of the main geological structures of an area in the Southernmost portion of the Reykjanes Ridge, between 57°5’ and 58°5’N. The axial volcanic ridges directions and the areas of the central volcanoes on the Reykjanes Ridge were mapped. In both East and West sides of the Mid-Atlantic Ridge, the normal faults were mapped and the geological orientation of the faulted planes analyzed. Data from the first multibeam bathymetric survey ever performed on the ridge were used for change detection analysis. Image differencing was performed, to detect changes on seafloor topography that might have happened within a time span of up to 23 years. The resulting images shows the intensity and value of change, where the negative values represent an increase in depth, and positive values represent a decrease in depth, or in other words, a decrease or increase in seafloor topographic elevation.